The Effectiveness Of Gestalt Game Techniques To Improve The Honest Character Of Teenagers - Rizky Anissa Irianti (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to test the effectiveness of the gestalt game technique to improvethe honest character of teenager.This study uses the One Group Pretest Posttest Design. The samples taken inthis study were 11 teenagers consisting of one experimental group. Sampling using randomsampling technique. The method of collecting and using an honest character questionnare.The data analysis Paired sample t-test.The results of this study indicate that the gestalt game technique is effectiveforimproving the honest character of teenager. This is evidenced by the results of the pairedsample t-test with a probability value of sig (2-tailed) 0,001<0,05. Basedon the results of theanalysis and discussion, there is a difference in the average score of the honest characterquestionnaire 9,80%, from the gestalt equation that is effective for improving the honestcharacter of teenager.